Forging National Character in the Digital Age 4.0: The Vital Role of Humans in Integrated Islamic Education - R Dedi Supriatna; Neng Vera Fachriyah; Tatang Muh Nasir (STAI Hubbulwathan Duri, 2023)
One of the key factors in the formation of national character and identity is Islamic religious education. Islamic religious education must be able to transform into a spirit that guides technology so that it is always useful in human existence in this digital 4.0 era when communication originating from a certain matter becomes global. In order to strengthen the formation of national character, this research looks for ways to incorporate science and technology into Islamic religious education. The research methodology used in this study is a qualitative descriptive research method that describes the current conditions of Islamic religious education learning and its relation to the nation's character building. The result of this research is that Islamic religious education should not be monolithic but must be integrated with non-religious subjects as well as science and technology so that today's young generation are willing and interested in studying religion well and Islamic religious education can be of value. which colors every skill and profession of Indonesian citizens, so that the morals and morals of the nation develop well according to the example of the Prophet Muhammad and aspired to by the state.